Lucas Wavelet Analysis of the Squeeze Film Characteristics Between a Sphere and a Flat Plate of Couple Stress Fluid Model - Shiralashetti, S. C.; Sangolli, A. M.; Vatsala, N. T. (Communications in Mathematics and Applications, 2025)
This study presents a numerical examination of the influence of couple stresses on the squeeze film behavior between a sphere and a flat plate, grounded in microcontinuum theory. The revised Reynolds equation that regulates the squeezing film pressure is formulated by employing the Stokes constitutive equations to incorporate the couple stress effects resulting from the lubricant mixed with distinct additives. Lucas wavelet based numerical scheme is developed for the numerical solution of the governing modified Reynolds equation. The numerical solution indicates that the presence of couple stresses results in an increase in the film pressure. Overall, the effects of couple stress, as defined by the couple stress parameter, lead to an enhancement in the load-carrying capacity when compared to the traditional Newtonian-lubricant scenario. The characteristics of the squeeze film in the system are enhanced.